Clinical and laboratory associations of mannose-binding lectin in 219 adults with IgG subclass deficiency - Barton, James C. (BMC Immunol, 2019)
BACKGROUND: Mannose-binding lectin (MBL) deficiency may increase risk of respiratory tract infection in adults unselected for IgG or IgG subclass levels. In a retrospective study, we sought to determine associations of serum MBL levels with clinical and laboratory characteristics of unrelated non-Hispanic white adults at diagnosis of IgG subclass deficiency (IgGSD). We computed the correlation of first and second MBL levels expressed as natural logarithms (ln) in a patient subgroup. We compared these characteristics of all adults with and without MBL ≤50 ng/mL: age; sex; body mass index; upper/lower respiratory tract infection; diabetes; autoimmune condition(s); atopy; other allergy; corticosteroid therapy; and subnormal serum IgG subclasses, IgA, and IgM. We performed logistic regression on MBL ≤50 ng/mL (dichotomous) using the three independent variables with the lowest values of p in univariate comparisons. RESULTS: There were 219 patients (mean age 51 ± 13 y; 82.5% women). Thirty-six patients (16.4%) had MBL ≤50 ng/mL. Two MBL measurements were available in 14 patients. The median interval between the first and second measurements was 125 d (range 18–1031). For ln-transformed data, we observed adjusted r(2) = 0.9675; Pearson correlation coefficient 0.9849; and p < 0.0001. Characteristics of patients with and without MBL ≤50 ng/mL did not differ significantly in univariate comparisons. We performed a regression on MBL ≤50 ng/mL using: subnormal IgM (p = 0.0565); upper respiratory tract infection (p = 0.1094); and body mass index (p = 0.1865). This regression revealed no significant associations. Conclusions: We conclude that the proportion of the present IgGSD patients with serum MBL ≤50 ng/mL is similar to that of healthy European adults. MBL ≤50 ng/mL was not significantly associated with independent variables we studied.